2021
DOI: 10.3389/fmed.2021.617378
|View full text |Cite
|
Sign up to set email alerts
|

Novel Cephalosporins in Septic Subjects and Severe Infections: Present Findings and Future Perspective

Abstract: In past decade, cephalosporins have developed significantly, and data regarding novel cephalosporins (i.e., ceftobiprole, ceftaroline, ceftolozane/tazobactam, ceftazidime/avibactam, and cefiderocol) within septic and bacteremic subjects are rising. These compounds generally offer very promising in vitro microbiological susceptibility, although the variability among gram-negative and -positive strains of different cohorts is noticed in the literature. We require further pharmacological data to measure the best … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 86 publications
0
10
0
Order By: Relevance
“…After liver transplantation, the risk of bacterial infections fluctuates over time, and clinicians should be aware of the differences between early infections (<1 month) with a high risk of community-acquired infections and latent infections in which the risk of opportunistic infections and hospital-acquired pathogens increases with prolonged immunosuppression and hospitalization ( Figure 1 ) [ 116 , 117 , 118 , 119 , 120 ].…”
Section: Discussionmentioning
confidence: 99%
“…After liver transplantation, the risk of bacterial infections fluctuates over time, and clinicians should be aware of the differences between early infections (<1 month) with a high risk of community-acquired infections and latent infections in which the risk of opportunistic infections and hospital-acquired pathogens increases with prolonged immunosuppression and hospitalization ( Figure 1 ) [ 116 , 117 , 118 , 119 , 120 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ceftazidime, a third-generation cephalosporin has a high importance in human medicine and it is used to treat severe infections. It is a major concern that the use of ceftazidime in food animals can promote resistance to other cephalosporins, such as ceftriaxone, used in humans and vice versa [ 38 ]. Although cephalosporins are not approved for use in poultry, the administration of these drugs in poultry and turkey farms is an emerging problem.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, novel beta-lactams/beta-lactams inhibitors combinations such as ceftazidime/ avibactam (C/A), meropenem/vaborbactam (M/V) and imipenem/relebactam (I/R) significantly reduced mortality patients with carbapenem-resistant Enterobacteriaceae infections [27][28][29]. Notably, C/A is an intravenous combination of a third-generation cephalosporin with the non-β-lactam/β-lactamase inhibitor avibactam, with activity against ESBL-producing bacteria, P. aeruginosa, and KPC or OXA-48 carbapenemase-producing bacteria [28,29]. Sun et al reported that C/A significantly reduced short-term mortality among SOT recipients with CPE infections compared with salvage regimens [30].…”
Section: Discussionmentioning
confidence: 99%